Confrontation with a live subretinal parasite - Khadka, Simanta; Byanju, Raghu Nandan; Pradhan, Sangita (Nepalese Journal of Ophthalmology, 2019)
Background: Parasitic infestation of the eyes are a major cause of ocular diseases across the globe. Filarial and filarial-like nematodes top the list of the nematodes that affect the eye.Case: A rare case of live sub retinal worm is reported in a 25 years old apparently healthy young male. The case presented with unilateral loss of vision and floaters in the affected eye. Upon examination a live subfoveal worm was identified with continuous wriggling movements and diffuse retinal edema. The worm was removed surgically and sent for parasitological examination.Observation: The worm was identified microscopically as Loa Loa. However detailed histopathological examination could not be incorporated. The patient’s vision improved to 6/12 (0.30 Log MAR) from the initial presentation of 3/60 (1.30 Log MAR) after three months follow-up.Conclusion: The rare sub retinal live worm presents a challenge in management. The management depends upon the location and viability of the parasite. Surgical management is aimed at worm removal and vision preservation.